2013
DOI: 10.1093/eurjhf/hfs151
|View full text |Cite
|
Sign up to set email alerts
|

Response to cardiac resynchronization therapy in elderly patients (≥70 years) and octogenarians

Abstract: AimsCardiac resynchronization therapy (CRT) leads to reverse ventricular remodelling, improved functional capacity, and better clinical outcome in patients with advanced chronic heart failure, reduced ejection fraction, and evidence of ventricular conduction delay, who are under optimal medical therapy. This study investigated whether these benefits can be extrapolated to older patients, typically not included in randomized clinical trials. Methods and resultsConsecutive patients who received a CRT device betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 25 publications
(25 reference statements)
2
35
0
7
Order By: Relevance
“…Two-hundred and thirtyseven were retrieved for analysis of titles and abstracts and 49 of these were selected for further analysis of the full-length article. Eighteen were considered eligible for inclusion 3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 99%
“…Two-hundred and thirtyseven were retrieved for analysis of titles and abstracts and 49 of these were selected for further analysis of the full-length article. Eighteen were considered eligible for inclusion 3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 99%
“…46 In addition, although very few older adult patients were enrolled in the major trials evaluating CRT, several small observational studies have demonstrated that appropriately selected octogenarians experience reduced symptoms, reverse ventricular remodeling, and improved exercise tolerance and quality of life following CRT implantation. 201 Therefore, based on currently available evidence, CRT is a reasonable option in selected patients with persistent HF symptoms despite medical therapy who meet criteria for implantation.…”
Section: Older Adultsmentioning
confidence: 99%
“…Nonrandomized studies have found similar reversals of left ventricular remodeling for old and young patients after CRT placement (11)(12)(13)(14).…”
Section: In a Substudy Of Then Madit-crt (Multicentermentioning
confidence: 83%